Determinasi Faktor yang Mempengaruhi Perilaku Pasien dalam Penggunaan Sistem Pendaftaran Online Berdasarkan Model UTAUT - Adhyka, Nurmaines; Rahmaddian, Tosi; Aisyiah, Intan Kamala; Hanum, Novia Zulfa; Azzahra, Muthia (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2025)
Online registration services, which are designed to enhance accessibility and efficiency, remain underutilized in one Type C hospital in Padang. This study aims to analyze the factors influencing patient behavior in using the online registration system based on the Unified Theory of Acceptance and Use of Technology (UTAUT). A quantitative cross-sectional design was employed involving 98 respondents selected through simple random sampling. The variables examined included performance expectancy, effort expectancy, social influence, facilitating conditions, demographic factors, and prior experience. Data were analyzed using chi-square tests and multiple logistic regression. The findings show that 55.1% of respondents had not optimally used the online registration system. Several factors were significantly associated with usage behavior, including age, gender, performance expectancy, effort expectancy, social influence, facilitating conditions, and experience (all p < 0.01). Multivariate analysis indicated that effort expectancy was the most dominant factor influencing patient behavior (OR ≈ 28). These results highlight that perceived ease of use is the key determinant of patients’ adoption of digital services. It is concluded that enhancing patients’ digital literacy, simplifying the application interface, and strengthening supporting facilities are critical strategies to improve the utilization of onlineregistration systems in hospitals.